Acute calcific prevertebral tendinitis: rare cause of neck pain. Issue 3 (21st November 2014) - Chen, Chia‐Hsi; Lu, Ying‐Chou; Wong, Tak‐Yee
Abstract : Case: We report a case of acute calcific prevertebral tendinitis and discuss the clinical signs, symptoms, and radiologic findings of the disease. Outcome: This 47‐year‐old man suffered from neck pain, odynophagia, and sore throat for 2 days. Acute calcific prevertebral tendinitis was noted. This disease, brought on by prolonged minor repetitive tendon injury, is an often overlooked cause of acute neck pain. The typical radiologic appearances of the disease include the calcification of the anterior surface of the C1–C2 spine and smooth soft tissue swelling over the retropharyngeal space. Conclusion: Generally this disease is benign and may be misdiagnosed as deep neck infection. Drainage on this patient would be considered malpractice.